THE USE OF STEVIA AND MONK FRUIT SWEETENERS FOR SUGAR REPLACEMENT IN GREEN TEA AGAR JELLIES - Adisak Akesowan; Anchan Choonhahirun (Food ScienTech Journal, 2021)
This study aimed to develop healthy agar jellies with low-sugar content, linking to a decreased risk for heart attack, diabetes, and other chronic diseases. Two natural non-nutritive sweeteners, stevia and monk fruit were studied at 25%, 50%, 75%, and 100% sugar replacement based on the equivalent sucrose sweetness. The physical properties assessed on the total soluble solids, firmness, color, and syneresis. Still, the sensory attributes on color, taste, flavor, texture, and overall acceptability was evaluated by a 9-point hedonic scale. The more sugar replacement lowered the total soluble solids but increased the gel firmness (p<0.05) and the lightness (L*). The syneresis declined in reduced-sugar jellies with stevia and monk fruit against the whole sugar jellies. The stevia and monk fruit replacement affected agar jellies' taste and flavor attributes (p<0.05). Jellies with 50% and 75% sugar replacement, either stevia or monk fruit, were preferred over 25% and 100% replacement. The jelly with 50% stevia was the optimal formulation.